81.6k views
14 votes
If a=under root s(s-a)(s-b)(s-c) then the value of a, when a =3 b =4c = 5 and s =a+b+c by 2

User Safwan
by
5.2k points

1 Answer

4 votes

Answer:

6

Explanation:

Here it's given that ,


\sf\red{\longrightarrow} A=√(s(s-a)(s-b)(s-c))

Also ,


\sf\red{\longrightarrow} s =(a+b+c)/(2)

And we need to find out the value of A , when

  • a = 3
  • b = 4
  • c = 5

So , on substituting the respective values to find s we have ,


\sf\red{\longrightarrow} s =(3+4+5)/(2)=(12)/(2)=\bf{6}

Now let's find out A as ,


\sf\red{\longrightarrow} A = √(6(6-3)(6-4)(6-5)) \\


\sf\red{\longrightarrow}A =√(6 * 3 * 2 * 1)\\


\sf\red{\longrightarrow} A = √(3^2 * 2^2 *1^2)\\


\sf\red{\longrightarrow}A = 3*2\\


\sf\red{\longrightarrow}\boxed{\qquad \blue{\bf A = 6 \qquad}}

User Vivek Mehta
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.